2009
DOI: 10.1007/s10549-009-0468-0
|View full text |Cite
|
Sign up to set email alerts
|

FEC versus sequential docetaxel followed by epirubicin/cyclophosphamide as adjuvant chemotherapy in women with axillary node-positive early breast cancer: a randomized study of the Hellenic Oncology Research Group (HORG)

Abstract: International audienceA randomized multicenter phase III study was conducted to compare the sequential docetaxel followed by epirubicin/cyclophosphamide combination with that of FEC regimen as adjuvant chemotherapy in women with axillary node-positive early breast cancer. Seven hundred and fifty-six women with axillary lymph node-positive breast cancer were randomized to receive either 4 cycles of docetaxel (100 mg/m) followed by 4 cycles of epirubicin (75 mg/m) plus cyclophosphamide (700 mg/m) (experimental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 14 publications
3
24
2
Order By: Relevance
“…Hematological toxicity and its complications are the greatest challenge in adjuvant chemotherapy for breast cancer. Our data analysis has shown that hematological toxicity, especially neutropenia, is the main side effect of anthracycline and taxane-based chemotherapy, as also observed in the NSABP-B-28 and the PACS-01 trials [10,12,21]. We found myelotoxicity to be the most common toxicity of grade 3/4 for both groups.…”
Section: Non-hematological Toxicitysupporting
confidence: 75%
See 2 more Smart Citations
“…Hematological toxicity and its complications are the greatest challenge in adjuvant chemotherapy for breast cancer. Our data analysis has shown that hematological toxicity, especially neutropenia, is the main side effect of anthracycline and taxane-based chemotherapy, as also observed in the NSABP-B-28 and the PACS-01 trials [10,12,21]. We found myelotoxicity to be the most common toxicity of grade 3/4 for both groups.…”
Section: Non-hematological Toxicitysupporting
confidence: 75%
“…In summary, taxanes have been shown in various trials to be a feasible treatment option [15,21,24]. Pooled data on the side effects from 4 trials (including the ADEBAR trial) demonstrate that taxane-containing chemotherapy is acceptable even for elderly patients [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taxanes – paclitaxel and semisynthetic docetaxel (DT) – are approved as first-line treatment for non-small cell lung cancer (NSCLC) [6,7], breast [8,9] and ovarian [10] carcinomas and are also used in the treatment of numerous other malignancies [11,12,13,14,15]. Paclitaxel is a natural alkaloid isolated from Taxus brevifolia, whereas DT is a semi-synthetic compound produced from 10-deacetylbaccatin III found in Taxus baccata [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a concern about the sequencing of these two drugs. In a recent randomized phase III study by the Hellenic Oncology Research Group, three weekly docetaxel followed by epirubicin/cyclophosphamide (E/C) combination was compared with epirubicin/cyclophosphamide/5-fluorouracil (FEC) regimen as adjuvant chemotherapy in women with axillary node-positive early breast cancer (1). Five-year disease-free survival was found to be better in the sequential docetaxel followed by E/C group (72.6 vs. 67.2%, P = 0.041).…”
mentioning
confidence: 99%